THE URGENCY OF REGULATING THE MISUSE OF PERSONAL DATA POSSESSION BY E-COMMERCE FROM THE PERSPECTIVE OF COMPETITION LAW - Amri, Prima (Domus Legalis Cogitatio, 2024)
The era of the digital economy has increased global trade transactions, giving rise to e-commerce companies that utilize the internet, websites, and applications to carry out trading activities in goods and services. This transformation has led to a change in viewing personal data as a commodity, so that e-commerce practices often take possession of personal data. Departing from this background, this study analyzes how the existing business competition law provisions anticipate the mastery of private data by e-commerce. This study uses a normative juridical method, with a legal-statutory approach and a conceptual approach. The results of the study show that mastery of personal data is indeed permitted in the Personal Data Protection Law, but it is necessary to pay attention to its impact on e-commerce business competition in Indonesia. The practice of controlling personal data has the potential to be misused and can result in monopolistic practices and/or unfair business competition. Current business competition legal instruments and the Business Competition Supervisory Commission (KPPU) are still limited in conducting investigations related to the practice of mastery of personal data by e-commerce which involves market advertising, definition of the e-commerce market, measuring market power, and reviewing mergers. It is necessary to formulate separate regulations regarding the prohibition of controlling personal data which can result in monopolistic practices and/or unfair business competition, both in the revision of the Business Competition Law and other related regulations.